Holocene tree line changes in the Canadian Cordillera are controlled by climate and topography. (2nd December 2016) - Schwörer, Christoph; Gavin, Daniel G.; Walker, Ian R.; Hu, Feng Sheng
Abstract: Aim: Although ongoing climate change is expected to lead to an upward shift of tree lines in mountain areas, evidence for widespread tree line advances remains scarce, implying secondary controls on tree line dynamics at the local scale. We aim to determine if vegetation change in response to past warm periods was regionally synchronous or if local factors such as topography, geomorphology or fire caused divergent local responses. Location: The Canadian Cordillera in south‐eastern British Columbia (Canada). Methods: We analysed post‐glacial sediments from three lakes at or just below the present tree line for macrofossils, pollen and charcoal to infer past local forest composition, density, dynamics and fire disturbance. Results: At two lakes (Windy and Redmountain), tree macrofossil concentrations were highest in the warmer‐than‐present Early Holocene (11, 700–7000 cal.bp ), indicating higher forest density and tree line position during this time period. At the third lake (Thunder), macrofossil concentrations were low during the Early Holocene and reached maximum values in the mid‐Holocene (7000–3000 cal.bp ). The divergent vegetation dynamics and species composition at Thunder Lake suggest that moisture availability may have limited the establishment of closed forests on steep south‐facing slopes or shallow soils in the Early Holocene. Main conclusions: Summer temperature was the main driver of tree line dynamics over millennial to decadal time‐scales. Closed forests, however, occurred only in areas of adequate moisture availability, which is controlled by topography and geomorphology. We therefore expect a rapid upward shift of tree lines during the 21st century in response to warmer temperatures, but only where deep soils or favourable aspects provide sufficient moisture for tree growth. Upward forest expansion will therefore be patchy and occur first in favourable microsites.